Effects of three-dimensional Cu/Nb interfaces on strengthening and shear banding in nanoscale metallic multilayers. (15th October 2020) - Chen, Y.; Li, N.; Hoagland, R.G.; Liu, X.-Y.; Baldwin, J.K.; Beyerlein, I.J.; Cheng, J.Y.; Mara, N.A.
Abstracts: Manipulation of the atomic-scale structure of two-dimensional (2D) interfaces have been shown to provide nanocomposites with enhanced strength, deformability, and radiation damage resistance. In comparison with 2D interfaces, here we investigate the mechanical response of nanocomposites containing three-dimensional (3D) Cu/Nb interfaces consisting of a chemical/structural gradient separating pure Cu and Nb layers, through which the lattice mismatch between face-centered cubic Cu and body-centered cubic Nb is accommodated over a distance of several nanometers. It is demonstrated that 3D interfaces increase the yield and flow strength by 50% and 22%, respectively, over composites containing 2D interfaces at similar layer thicknesses. After 14% compressive strain, the onset of shear banding results in co-deformation of both Cu and Nb phases within and outside of the shear band. We conclude with a discussion of the role of interface structure in shear band formation and growth in 3D Cu/Nb. Graphic abstract: Image, graphical abstract